A material-property-dependent sub-grid drag model for coarse-grained simulation of 3D large-scale CFB risers - Zhu, Li-Tao; Liu, Yuan-Xing; Tang, Jia-Xun; Luo, Zheng-Hong (Chemical engineering science, 2019)
[Display omitted] •A material-property-dependent sub-grid drag modification is developed.•The newly constituted correction model is verified by highly-resolved simulation results.•Results reveal an essential dependence of sub-grid drag correction on material properties.•Hydrodynamic validation predictions achieve good accordance with various experiments. Developing, verifying and validating sub-grid methods is of crucial significance for enabling accurate coarse-grained two-fluid modeling of rapid gas-fluidized flows. However, very few studies in the literature so far have been focused on how the sub-grid modification depends on material properties. As an extension of previous sub-grid efforts, this fundamental investigation attempts to derive a material-property-dependent drag modification based on generated data from an initially homogeneous state of periodic gas-particle suspensions. The newly constituted model is then verified by highly-resolved two-fluid simulation results. We further validate the accuracy of model predictions via systematic assessments to experimental results that encompass a wide variety of material properties in five three-dimensional large-scale circulating fluidized bed (CFB) risers. Besides, we introduce a deviation index (DI) to quantify the predictive capability of the extended model. Computational results demonstrate an essential dependence of drag correction on material properties as an additional factor. Hydrodynamic validation predictions achieve satisfactory accordance with experiments. The current model is potential to serve as a more general tool for efficiently reducing the number of pilot-scale tests and effectively designing and controlling industrial process devices.